Microstructure-property relations of biphasic calcium phosphate obtained by hot pressing process - Krai Kulpetchdara (2020)
© 2019 University of Novi Sad, Faculty of Technology. All rights reserved. Biphasic calcium phosphate (BCP) was fabricated through hot pressing process from hydroxyapatite (HA) starting powder synthesized by a peroxide-based precipitation method and dried at 250 °C. The synthesized HA powder contained some calcium hydrogen phosphate (CHP) as a minor phase. In this work, the dense BCP ceramics with a mixture of HA and β-TCP phases were successfully obtained by hot pressing at temperature ranging from 700–1100 °C. The amount of HA phase in the hot pressed samples decreased with increasing sintering temperature from 700 to 900 °C, while the amount of β-TCP exhibited an opposite trend. The relations between the microstructure and mechanical properties of the dense BCP ceramics sintered in the temperature range 700–1100 °C were investigated. The sample hot pressed at 800 °C has a dense structure with the highest hardness (4.86 ± 0.19 GPa) and the lowest fracture toughness (0.80 ± 0.01 MPa·m1/2). In addition, biocompatibility of apatite layer formed after immersion in simulated body fluid (SBF) for 14 days can be observed by SEM images. The results revealed that the samples hot-pressed at 800 and 900 °C were covered by calcium phosphate (CaP) crystal layer indicating the strong interaction of BCP ceramics and SBF.